Psychiatric Comorbidities in Children With ASD: Autism Centre Experience - Ivanović, Iva (Frontiers in Psychiatry, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder with social communication deficits, restricted interests and repetitive behaviours. In this lifelong condition the core features that cause impairment may also be expanded by behavioural and emotional problems. Individuals with ASD are likely to experience a higher prevalence of common mental disorders compared to the typically developed individuals. This high epidemiological burden of various psychiatric disorders among ASD population encourages further research and improvement in diagnostic practice in ASD and comorbid disorders. In this brief research report of a cross-sectional study it was aimed to estimate the psychiatric comorbidity prevalence and describe their general characteristics in children with ASD in Autism Centre in Montenegro. The study population consisted of 152 patients who were diagnosed with ASD, 117 male and 35 female and the mean age (SD) was 8.02 (4.26). In this brief research report prevalence of children with ASD with at least one psychiatric comorbidity was 36.84 %. Only one psychiatric comorbidity disorder was reported in 17.16%, two in 9.87%, three in 8.55% and in 0.66% patients four other psychiatric disorders. Psychiatric disorders present in this population sample were attention deficit hyperactivity disorder (17.76%), conduct disorder (13.10%), disruptive mood dysregulation disorder (9.87%), anxiety disorder and insomnia (7.89%), elimination disorder (3.29%) and depression (1.97%).